How Does (And Doesn’t) Education Enable Individual Skills Development and Employment - Dibekulu Alem Asegu (Research Synergy Foundation, 2023)
This narrative review examines the degree to which authors contend that education contributes to or hinders the development of an individual skill that leads to employment. Besides, it provides an overview of the kinds of training that allow people to develop their skills and find employment globally and within Ethiopia following a dependency model (employability on education and skill development). The literature review examines the importance of education for employment and developing skills and talents. A few of the most significant policy issues, employment strategies, and challenges are also reviewed accordingly. Consequently, it might be possible to conclude that a person's education should align with the kind of job that organizations and individuals are seeking around the globe, including in Ethiopia. In the end, following a thorough literature review, this research provides some recommendations to enhance education for upcoming progress.